Frequency of Depression in Young Patients with Diabetes Mellitus - Abdullah, .; Hussain, Tariq (Biological and Clinical Sciences Research Journal, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder associated with numerous physical and psychological complications. Depression is a common comorbidity in diabetic patients, significantly impacting self-care, glycemic control, and quality of life. Objective: To determine the frequency of depression in young patients with diabetes mellitus aged 15–45 years. Methods: This descriptive cross-sectional study was conducted at the Department of Medicine, PAEC General Hospital Islamabad from October 2024 till March 2025. A total of 122 diabetic patients aged 15–45 years, with a duration of diabetes over six months, were enrolled through non-probability consecutive sampling. Sociodemographic and clinical data were collected using a structured proforma. Results: Among 122 patients, 49 (40.2%) were diagnosed with depression. Depression was more common among females (45.3%) than males (34.5%). It was more prevalent in patients with lower income (<25,000 PKR/month: 57.9%), illiterate individuals (72.2%), and those with longer diabetes duration (>10 years: 52%). Higher rates were also observed among smokers (54.8%) and those with hypertension (50%). Depression severity ranged from mild (15.6%) to moderate (14.8%) and severe (9.8%). Significant associations were found between depression and income (p=0.01), education level (p=0.003), smoking (p=0.04), and hypertension (p=0.05). Conclusion: Depression is highly prevalent among young patients with diabetes, particularly those with lower socioeconomic status, poor education, and longer disease duration. Routine mental health screening and integrated psychological support should be incorporated into diabetes management to improve overall outcomes.